ASPEK PENANGKAPAN SUMBERDAYA IKAN KERAPU SUNU (Plectropomus leopardus) DI PERAIRAN PULAU SARAPPO KABUPATEN PANGKEP PROVINSI SULAWESI SELATAN - Isnadah Isnadah; Ernaningsih Ernaningsih; Ihsan Ihsan (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
Grouper fishing (Plectropomus leopardus) has increased resource exploitation, this effort has an impact on the sustainability of sunu grouper resources in Spermonde waters. The purpose of this study is the fishing aspect (time of the fishing season, parameters of oceanography physics of waters and sunu grouper fishing areas). This research uses case and field study methods. The results of the study show that 1) the fishing season shows that the variation of seasons, especially the famine season, will provide opportunities for sunu grouper fish to increase recruitment and restore grouper their population. 2) Aquatic oceanographic parameters affect the production and productivity of fishermen's catches. 3) Sunu grouper fishing areas are sufficiently available for fishermen fishing based on environmental factors in Spermonde waters.